A review of requirement engineering: requirement analysis and documentation. - Jusoh, Yusmadi Yah; Mohd Ali, Norhayati (2001)
"The hardest single part of building a software system is deciding precisely what to build. No other part of the conceptual work is as difficult as establishing the detailed technical requirement ... No other part of the work so cripples the resulting system if done wrong. No other part is as difficult to rectify later. "[Brooks. 87] This paper presents an exposition of requirement engineering concepts and challenges. It is argued that doing requirements is a difficult task and its critical problems are identified. The activities involved in requirements engineering are described and the aspects of an iterative process are presented. The state of art of the research in two of requirements activities: requirements analysis and documentation are described. The paper ends with a detailed proposal for an investigation of CASE tools support would considered as communicative and helping the activity the requirement analysis and documentation.